Návrh optimálního léčebného postupu v léčbě nízkorizikového karcinomu štítné žlázy - Vlček, Petr; Nováková, Dagmar; Vejvalka, Jan; Zimák, Jaroslav; Křenek, Martin; Vošmiková, Květuše; Smutný, Svatopluk; Bavor, Petr; Astl, Jaromír; Lukáš, Jindřich (Vnitrni lekarstvi, 2015)
INTRODUCTION: The incidence of well-differentiated low-risk thyroid cancer have increased globally over the last three decades. Thyroid cancer treatment relates to a suitable surgical procedure and the use of adjuvant radio-iodine therapy in selected patients. Evaluation of prognostic factors and risk stratification are critical for determining appropriate treatment. Survival of patients with low-risk thyroid cancer is excellent. Appropriate choice of medical treatment resulted in full recovery in most patients. Relapse risk increases with the size of the primary tumor, along with the findings of the risk factors in men. METHODS AND RESULTS: Our study included a total of 1 980 patients in whom were diagnosed T1a and T1b tumors between the years 2003 to 2012. The population included 1 675 women (84.6 %) of average age of 45.22 years and 305 men (15.4 %) of average age of 50.0 years. The bulk of the file represented papillary carcinomas (1 868; 94.4 %), and smaller group of follicular carcinomas (112; 5.6 %). Patients were divided into four groups according to tumor size. Patients were evaluated according to risk factors: unifocality no other risk factors, multifocality - more bearings in thyroid tumor, metastases in regional lymph nodes, distant metastases or combination of risk factors. Group A: In the monitored set of 678 patients with papillary and follicular microcarcinoma up to 5 mm, during histological input, the findings revealed one bearing (unifocal type of cancer) in 566 patients. Multifocality was found in 112 patients, local nodal metastasis were demonstrated in 24 cases and pulmonary metastasis was discove-red in 1 case. Group B: In this group there were 576 study patients with papillary and follicular microcarcinoma size of 5-10 mm. Histological findings were captured input one bearing carcinoma in 434 patients, 142 patients with multifocality, in 53 cases of local nodal metastasis, and 1 case of bone metastases. Group C: In this group there were 467 study patients with papillary and follicular microcarcinoma size 10-15 mm. The histological initial finding captured unifocal type of cancer in 344 patients, multifocality in 123 patients, in 45 cases local metastases and in 3 cases of pulmonary metastases. Group D: 259 patients were monitored in this group with breast size 16-20 mm. At the initial finding was captured one bearing cancer in 188 patients, multifocality in 71 patients, in 24 cases evidence of local metastases and 2 patients had a case of distant lung metastases. In patients in whom risk factors were found, radioiodine treatment was indicated. This included 744 patients. In this group of patients after a year or more, relapse was observed in 74 patients (9.94 %). In 1 236 patients who did not undergo radioiodine treatment, there was a relapse in 49 patients (3.96 %). CONCLUSION: Based on our analysis, it is necessary to stratify the risk of relapse according to risk factors. In case of missed radioiodine therapy in patients with low-risk cancer without confirmed risk factors, it is also necessary to have regular clinical, laboratory and ultrasound examination. It is important to distinguish patients with risk factors that may contribute to disease recurrence. Only in this way, on one hand we prevent excessive treatment of patients with low-risk thyroid cancer which leads to increased cost of health care, and on the other hand prevent reduced level of care for patients with an increase in relapses.
Keywords: kombinovaná terapie; radioizotopy jodu; Cross-Sectional Studies; Male; Combined Modality Therapy; Risk Factors; lokální recidiva nádoru; folikulární adenokarcinom; prognóza; Neoplasm Staging; tyreoidektomie; Thyroid Neoplasms; Adult; Aged; dospělí; mnohočetné primární nádory; mužské pohlaví; senioři; papilární adenokarcinom; Adenocarcinoma, Follicular; Thyroidectomy; Iodine Radioisotopes; Adenocarcinoma, Papillary; Lymphatic Metastasis; Neoplasms, Multiple Primary; Neoplasm Recurrence, Local; nádory štítné žlázy; lidé; ženské pohlaví; Humans; rizikové faktory; průřezové studie; Prognosis; lymfatické metastázy; Female; lidé středního věku; staging nádorů; Middle Aged